Cyber-Attack Resilient Design of Wide-Area PSS Considering Practical Communication Constraints - Prakash T.; Singh V.P.; Mohanty S.R. (My University, 2025)
This article presents cyber-attack resilient design of wide-area power system stabilizers (WAPSSs) for damping low-frequency oscillations considering practical communication constraints. The measurements estimated by phasor measurement units (PMUs) are inherent to communication constraints such as time-delay, packet drops, and cyber-attacks. In this article, the generator terminal bus frequencies (approximately representing respective rotor speeds) are estimated by PMUs and their differences are considered as input control signals to WAPSSs. In case if the communication constraints associated with transfer of estimated frequencies are not addressed properly then they may reduce the damping capability of WAPSSs. In this context, simple and time-efficient techniques are proposed to compensate time-delay and to predict input signals in case of data drops and attacks for improving the performance of WAPSSs. A cryptographic security by means of hashed algorithms is provided to remote signals for the detection of occurrence and period of cyber-attack. The parameters of WAPSSs are tuned using a hybrid optimization algorithm. The efficacy of proposed technique is validated on IEEE 39-bus system operating under different conditions. © 2007-2012 IEEE.